High-nitrogen duplex stainless steel and preparation method of strip of high-nitrogen duplex stainless steel
By adjusting the chemical composition and preparation process of high-nitrogen duplex stainless steel, the problems of poor corrosion resistance and difficult production in the existing technology are solved, and the corrosion resistance and mechanical properties of high-nitrogen duplex stainless steel are improved, reducing the risk of cracking.
Patent Information
- Application Number
- CN202411776426.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-14
AI Technical Summary
The existing nitrogen-containing duplex stainless steel has poor corrosion resistance and is difficult to produce, especially in hot forging and hot rolling, which is prone to brittle phase precipitation, increasing the risk of cracking.
The preparation method of high-nitrogen duplex stainless steel is adopted to control the forging and hot rolling temperatures to reduce the precipitation of brittle phases by adjusting chemical composition and process parameters, including preheating and rapid heating, multi-fire forging and three-rolling and three-annealing.
It improves the corrosion resistance and mechanical properties of high-nitrogen duplex stainless steel, reduces the risk of cracking, and meets the production requirements for corrosion resistance, mechanical properties and welding properties.
Smart Images

Figure BDA0005171579770000091 
Figure BDA0005171579770000092
Abstract
Description
Technical Field
[0001] The invention relates to duplex stainless steel, and in particular to a preparation method of high-nitrogen duplex stainless steel and a strip thereof. Background Art
[0002] In recent years, with the rapid development of my country's petrochemical and coal chemical industries, the containers used in these fields are facing increasingly harsh service environments. Especially under the action of harsh chemical media such as strong acids and alkalis, problems such as local pitting, stress corrosion and cavitation corrosion have become increasingly prominent. These problems not only affect the service life of the container, but may also pose a serious threat to production safety. At present, in order to solve these problems, related large containers are mainly made of stainless steel. However, in actual applications, after local welding using traditional welding materials, the containers often have disadvantages such as low strength and poor corrosion resistance. These defects limit the application range and reliability of the container, and therefore put forward higher requirements on the performance of the welding materials.
[0003] In order to improve the comprehensive performance of the container, the industry began to try to use nitrogen-containing duplex stainless steel strips for welding. This material not only has high strength and good wear resistance, but also has significant advantages in corrosion resistance.
[0004] However, the production of nitrogen-containing duplex stainless steel strip is not easy. During hot forging and hot rolling, if the temperature is too low, it will lead to the precipitation of brittle phases, thereby increasing the risk of cracking and may even cause the billet to be scrapped. Summary of the invention
[0005] The purpose of the present invention is to solve the technical problems that the existing nitrogen-containing duplex stainless steel has poor corrosion resistance and is difficult to produce, and to provide a method for preparing high-nitrogen duplex stainless steel and a strip thereof.
[0006] To solve the above technical problems, the technical solutions provided by the present invention are as follows:
[0007] A high nitrogen duplex stainless steel, the chemical composition of which, in terms of mass percentage, includes:
[0008] N: 0.15-0.35%, Cr: 24.5-26.5%, Ni: 8.0-11.0%, Mo: 3.4-3.9%, Mn: 1.5-3.5%, C≤0.001%, Si≤0.20%, P≤0.02%, S≤0.01%, and the balance Fe.
[0009] Furthermore, its chemical composition, in terms of mass percentage, includes:
[0010] N: 0.23-0.28%, Cr: 24.9-25.2%, Ni: 8.92-9.15%, Mo: 3.7-3.75%, Mn: 2.65-2.69%, C≤0.001%, Si≤0.20%, P≤0.02%, S≤0.01%, and the balance Fe.
[0011] Furthermore, its chemical composition, in terms of mass percentage, includes:
[0012] N: 0.28-0.33%, Cr: 25.2-25.6%, Ni: 8.41-8.95%, Mo: 3.75-3.77%, Mn: 2.69-2.73%, C≤0.001%, Si≤0.20%, P≤0.02%, S≤0.01%, and the balance Fe.
[0013] A method for preparing a high nitrogen duplex stainless steel strip comprises the following steps:
[0014] S1. Prepare the charge, melt the charge, and obtain a steel billet with the chemical composition after cooling;
[0015] S2. Grinding the surface of the steel billet to remove defects on the surface of the steel billet;
[0016] S3, preheating the steel billet after grinding at 560-640°C for 30 min, then heating the steel billet to 1180-1240°C at a heating rate of 150-200°C / min and keeping it warm for 1 h;
[0017] After the insulation is completed, the steel billet is forged with a deformation amount of 20%-40%, the start forging temperature is ≥1160℃, and the final forging temperature is ≥1040℃;
[0018] After forging is completed, air cooling is performed to obtain the forging blank;
[0019] S4, grinding the forging blank and blowing it with compressed air to remove the residual oxide scales from grinding;
[0020] S5. Heat the forging blank to 1180-1240°C at a heating rate of 190-240°C / min and keep it at that temperature for 1 hour;
[0021] After the heat preservation is completed, the forging billet is hot rolled, the starting rolling temperature is ≥1160°C, the final rolling temperature is ≥1040°C, and the hot rolling is completed and air-cooled to obtain a hot-rolled billet;
[0022] S6, heating the hot rolled slab to 1070-1180°C, and performing a solution treatment on the hot rolled slab for 30-60 minutes;
[0023] After the solution treatment, the hot rolled billet is immediately water cooled, and then the hot rolled billet is ground;
[0024] S7. The hot-rolled billet is subjected to three cold rolling, degreasing and continuous annealing to obtain a high nitrogen duplex stainless steel strip.
[0025] Furthermore, in step S1, the charge is metallic chromium, electrolytic nickel, metallic molybdenum, metallic manganese, pure iron and ferrochromium nitride with a particle size of ≯20 mm, and the nitrogen content in the ferrochromium nitride is greater than or equal to 10%.
[0026] Furthermore, in step S3, the steel billet is subjected to multi-forging, and the deformation amount of the multi-forging is 20%-40%.
[0027] Furthermore, in step S4, the pressure of the compressed air is 0.2-0.5 MPa.
[0028] Furthermore, in step S5, the forging billet is hot rolled, and the thickness of the hot rolled billet is 4.0-4.5 mm.
[0029] Further, step S7 is specifically as follows:
[0030] S7.1, feeding the hot rolled slab into a rolling mill for primary cold rolling, wherein the reduction rate of the primary cold rolling is 50%-60%, the rolling tension is 40-60KN, four passes are adopted and the reduction rate of the first pass is ≮25%, and a primary cold rolled strip with a thickness of 1.62-2.25mm is obtained;
[0031] The primary cold-rolled strip is degreased and cleaned using hot alkaline water at 35-45°C to obtain a primary cleaned strip;
[0032] The primary cleaning tape is fed into the annealing furnace at a tape speed of 0.7-1.2 m / min, and continuously annealed at 1050°C, and a primary annealing tape is obtained after cooling;
[0033] S7.2, feeding the primary annealed strip into a rolling mill for secondary cold rolling, wherein the secondary cold rolling reduction rate is 50%-55%, the rolling tension is 23-28KN, three passes are adopted and the first pass reduction rate is ≮22%, and a secondary cold rolled strip with a thickness of 0.75-1.13mm is obtained;
[0034] The secondary cold-rolled strip is degreased and cleaned with hot alkaline water at 35-45°C to obtain a secondary cleaned strip;
[0035] The secondary cleaning tape is fed into the annealing furnace at a tape speed of 2.0-3.0 m / min, and continuously annealed at 1050°C, and a secondary annealing tape is obtained after cooling;
[0036] S7.3, the secondary annealed strip is sent to the rolling mill for three cold rolling, the three cold rolling reduction rate is 45%-52%, the rolling tension is 16-25KN, three passes are used for rolling and the first pass reduction rate is ≮20%, and the three cold rolling strip with a thickness of 0.35-0.55mm is obtained:
[0037] The secondary cold-rolled strip is degreased and cleaned with hot alkaline water at 35-45°C to obtain a triple-cleaned strip:
[0038] The tertiary cleaned strip is fed into an annealing furnace at a strip speed of 6.0-8.0 m / min and continuously annealed at 1050° C. After cooling, a tertiary annealed strip is obtained, i.e., a high nitrogen duplex stainless steel strip.
[0039] Furthermore, in step S7, high-purity nitrogen is used for purging and cooling after continuous annealing, and the purging pressure is 0.2-
[0040] 0.5MPa, cooling rate is 130-150℃ / min;
[0041] In terms of mass percentage, hot alkaline water at 35-45°C is a mixture of 30% sodium hydroxide and 70% tap water.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] 1. The high nitrogen duplex stainless steel provided by the present invention can improve the corrosion resistance of the duplex stainless steel by increasing the N content to 0.15-0.35% (usually the N content is less than 0.15%), and on the other hand, can regulate the ratio of the two phases (austenite and ferrite) in the organization; by adjusting the addition ratio of different alloy elements, the high nitrogen duplex stainless steel meets the dual-phase requirements of austenite and ferrite, and utilizes the plasticity and toughness of austenite and the strength and hardness characteristics of ferrite to meet the production requirements for corrosion resistance, mechanical properties, weldability and other performance requirements.
[0044] 2. The preparation method of the high nitrogen duplex stainless steel strip provided by the present invention adopts the methods of preheating first and then rapidly heating and rapidly heating during forging and hot rolling, and controls the temperatures of forging and hot rolling to reduce the residence time of brittle phases such as χ phase, Laves phase, σ phase at 600-1000°C during forging and hot rolling, reduce the amount of brittle phase precipitation on the surface of the intermediate billet, and further avoid the problem of cracking during forging and hot rolling; the deformation amount is controlled at 20%-40%, so that the heat energy released by the steel billet during forging deformation can compensate for part of the heat loss, and at the same time can meet the grain size requirements.
[0045] 3. The preparation method of the high nitrogen duplex stainless steel strip provided by the present invention adopts a three-rolling and three-annealing method to gradually reduce the influence of work hardening on the nitrogen-containing duplex stainless steel; after continuous annealing, nitrogen purge is used for rapid cooling to reduce the residence time of the nitrogen-containing duplex stainless steel strip at 600-1000°C and minimize the precipitation of brittle phase.
[0046] 4. The preparation method of the high nitrogen duplex stainless steel strip provided by the present invention combines the melting points of each element and the precipitation temperature range of the brittle phase, adopts a suitable temperature for post-rolling heat treatment, eliminates the influence of grain boundary element segregation and harmful precipitation phases generated during the thermal deformation cooling process, ensures excellent mechanical properties and provides high-quality billets for subsequent cold rolling production. DETAILED DESCRIPTION
[0047] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] A high nitrogen duplex stainless steel, the chemical composition of which, in terms of mass percentage, includes: N: 0.15-0.35%, Cr: 24.5-26.5%, Ni: 8.0-11.0%, Mo: 3.4-3.9%, Mn: 1.5-3.5%, C≤0.001%, Si≤0.20%, P≤0.02%, S≤0.01%, and the balance Fe;
[0049] Alternatively, its chemical composition includes, by mass percentage: N: 0.23-0.28%, Cr: 24.9-25.2%, Ni: 8.92-9.15%, Mo: 3.7-3.75%, Mn: 2.65-2.69%, C≤0.001%, Si≤0.20%, P≤0.02%, S≤0.01%, and the balance Fe.
[0050] Alternatively, the chemical composition includes, by mass percentage: N: 0.28-0.33%, Cr: 25.2-25.6%, Ni: 8.41-8.95%, Mo: 3.75-3.77%, Mn: 2.69-2.73%, C≤0.001%, Si≤0.20%, P≤0.02%, S≤0.01%, and the balance Fe. Wherein:
[0051] C is used for deoxidation, but a high C content will affect the solubility of N, so the C content is less than or equal to 0.001%.
[0052] Cr is used to improve the corrosion resistance and strength of the material. The added Cr element will generate Cr on the surface of the steel ingot. 2 O 3 The film protects the internal materials, and the corrosion resistance will be significantly enhanced with the increase of Cr element content, but too high Cr content is conducive to the precipitation of harmful phases, affecting the stability of mechanical properties of high nitrogen duplex stainless steel; therefore, the Cr content is 24.5-26.5%.
[0053] Mn is used to increase the limiting solid solubility of N in high nitrogen duplex stainless steel. However, the combination of Mn and S will generate MnS type inclusions at the grain boundaries, resulting in a decrease in the pitting and intergranular corrosion resistance of duplex stainless steel. Mo is usually added to reduce the adverse effects of Mn. Adding Mn can also improve the forgeability (i.e. plasticity) of high nitrogen stainless steel. Therefore, the Mn content is 1.5-3.5%.
[0054] Mo is used to ensure the corrosion resistance of high nitrogen duplex stainless steel, and is also conducive to the generation of MoO on the surface of high nitrogen duplex stainless steel. 2 Protective film to prevent high nitrogen duplex stainless steel from further corrosion; Mo is about three times stronger than Cr in improving the corrosion resistance of high nitrogen stainless steel, but too high Mo content will promote the precipitation of harmful phases such as χ phase, σ phase, Laves phase, etc., and will increase the precipitation temperature of harmful phases, and expand the temperature range of brittle phase precipitation, reducing the toughness and plasticity of nitrogen-containing stainless steel; therefore, the Mo content is 3.4-3.9%.
[0055] Ni is a key element for forming austenite, and is used to promote the formation of an austenite crystal structure inside duplex stainless steel. By adding the Ni element, the crystal structure of ferrite can be transformed from a body-centered cubic (BCC) structure to a face-centered cubic (FCC) structure, thereby improving the plasticity, weldability, toughness and other properties of nitrogen-containing stainless steel. Therefore, the Ni content is 8.0-11.0%.
[0056] On the one hand, N can improve the corrosion resistance of duplex stainless steel, and on the other hand, it can also play a role in regulating the ratio of austenite and ferrite. While ensuring a high Ni content, the microstructure of duplex stainless steel is optimized by introducing a high content of N elements, so that the strength of duplex stainless steel is improved. Therefore, the N content is 0.15-0.35%.
[0057] A method for preparing a high nitrogen duplex stainless steel strip comprises the following steps:
[0058] S1. Prepare the furnace charge, which is metal chromium, electrolytic nickel, metal molybdenum, metal manganese, pure iron and ferrochrome nitride with a particle size of ≯20 mm, wherein the nitrogen content in the ferrochrome nitride is greater than or equal to 10%;
[0059] The charge is melted and cooled to obtain a steel billet with the chemical composition;
[0060] S2. Grinding the surface of the steel billet to remove defects on the surface of the steel billet;
[0061] S3, preheating the steel billet after grinding at 560-640°C for 30 min, then heating the steel billet to 1180-1240°C at a heating rate of 150-200°C / min and keeping it warm for 1 h;
[0062] After the insulation is completed, the steel billet is forged with a deformation amount of 20%-40%, the start forging temperature is ≥1160℃, and the final forging temperature is ≥1040℃;
[0063] After forging is completed, air cooling is performed to obtain the forging blank;
[0064] S4. Grind the forging blank and use compressed air to blow it to remove the residual oxide scales from grinding; the pressure of the compressed air is 0.2-0.5MPa;
[0065] S5. Heat the forging blank to 1180-1240°C at a heating rate of 190-240°C / min and keep it at that temperature for 1 hour;
[0066] After the insulation is completed, the forging billet is hot rolled, the starting rolling temperature is ≥1160°C, the final rolling temperature is ≥1040°C, and the hot rolling billet is air cooled after the hot rolling is completed to obtain the hot rolled billet, the thickness of the hot rolled billet is 4.0-4.5mm;
[0067] S6, heating the hot rolled slab to 1070-1180°C, and performing a solution treatment on the hot rolled slab for 30-60 minutes;
[0068] After the solution treatment, the hot rolled billet is immediately water cooled, and then the hot rolled billet is ground;
[0069] S7, cold rolling, degreasing and continuous annealing are performed on the hot rolled billet three times:
[0070] S7.1, feeding the hot rolled slab into a rolling mill for primary cold rolling, wherein the reduction rate of the primary cold rolling is 50%-60%, the rolling tension is 40-60KN, four passes are adopted and the reduction rate of the first pass is ≮25%, and a primary cold rolled strip with a thickness of 1.62-2.25mm is obtained;
[0071] The primary cold-rolled strip is degreased and cleaned using hot alkaline water at 35-45°C to obtain a primary cleaned strip;
[0072] The primary cleaning tape is fed into the annealing furnace at a tape speed of 0.7-1.2 m / min, and continuously annealed at 1050°C, and a primary annealing tape is obtained after cooling;
[0073] S7.2, feeding the primary annealed strip into a rolling mill for secondary cold rolling, wherein the secondary cold rolling reduction rate is 50%-55%, the rolling tension is 23-28KN, three passes are adopted and the first pass reduction rate is ≮22%, and a secondary cold rolled strip with a thickness of 0.75-1.13mm is obtained;
[0074] The secondary cold-rolled strip is degreased and cleaned with hot alkaline water at 35-45°C to obtain a secondary cleaned strip;
[0075] The secondary cleaning tape is fed into the annealing furnace at a tape speed of 2.0-3.0 m / min, and continuously annealed at 1050°C, and a secondary annealing tape is obtained after cooling;
[0076] S7.3, the secondary annealed strip is sent to the rolling mill for three cold rolling, the three cold rolling reduction rate is 45%-52%, the rolling tension is 16-25KN, three passes are used for rolling and the first pass reduction rate is ≮20%, and the three cold rolling strip with a thickness of 0.35-0.55mm is obtained:
[0077] The secondary cold-rolled strip is degreased and cleaned with hot alkaline water at 35-45°C to obtain a triple-cleaned strip:
[0078] The tertiary cleaned strip is fed into an annealing furnace at a strip speed of 6.0-8.0 m / min and continuously annealed at 1050° C. After cooling, a tertiary annealed strip is obtained, i.e., a high nitrogen duplex stainless steel strip.
[0079] In step S7, high-purity nitrogen is used for purging and cooling after continuous annealing, the purging pressure is 0.2-0.5 MPa, and the cooling rate is 130-150°C / min.
[0080] In step S7, the hot alkaline water at 35-45° C. is prepared by mixing 30% sodium hydroxide and 70% tap water, in terms of mass percentage.
[0081] Specific examples are given below.
[0082] Example 1
[0083] A method for preparing a high nitrogen duplex stainless steel strip comprises the following steps:
[0084] S1. Prepare the charge. The chemical composition of the charge includes, by mass percentage, N: 0.15-0.35%, Cr: 24.5-26.5%, Ni: 8.0-11.0%, Mo: 3.4-3.9%, Mn: 1.5-3.5%, C≤0.001%, Si≤0.20%, P≤0.02%, S≤0.01%, and the balance Fe;
[0085] The charge is metallic chromium, electrolytic nickel, metallic molybdenum, metallic manganese, pure iron and ferrochromium nitride with a particle size of ≯20mm, and the nitrogen content in the ferrochromium nitride is greater than or equal to 10%;
[0086] The charge is melted and cooled to obtain a steel billet with the chemical composition;
[0087] S2. Grinding the surface of the steel billet to remove defects on the surface of the steel billet;
[0088] S3, preheating the steel billet after grinding at 600°C for 30 min, then heating the steel billet to 1200°C at a heating rate of 160°C / min and keeping it at that temperature for 1 h;
[0089] After the insulation is completed, the steel billet is forged with a deformation amount of 35%, the starting forging temperature is ≥1160℃, and the final forging temperature is ≥1040℃;
[0090] After forging is completed, air cooling is performed to obtain the forging blank;
[0091] S4. Grind the forging blank and use compressed air to blow it to remove the residual oxide scale from the grinding. The pressure of the compressed air is 0.35MPa.
[0092] S5, heating the forging blank to 1200°C at a heating rate of 210°C / min and keeping the temperature for 1h;
[0093] After the insulation is completed, the forging billet is hot rolled, the starting rolling temperature is ≥1160°C, the final rolling temperature is ≥1040°C, and the hot rolling billet is air cooled after the hot rolling is completed to obtain the hot rolled billet, and the thickness of the hot rolled billet is 4.2mm;
[0094] S6, heating the hot rolled slab to 1150° C. and performing a solution treatment on the hot rolled slab for 30 minutes;
[0095] After the solution treatment, the hot rolled billet is immediately water cooled, and then the hot rolled billet is ground;
[0096] S7, cold rolling, degreasing and continuous annealing are performed on the hot rolled billet three times:
[0097] S7.1, feeding the hot rolled slab into a rolling mill for primary cold rolling, wherein the reduction rate of the primary cold rolling is 56%, the rolling tension is 55KN, four passes are adopted and the reduction rate of the first pass is ≮25%, and a primary cold rolled strip with a thickness of 1.85mm is obtained;
[0098] The primary cold-rolled strip is degreased and cleaned using hot alkaline water at 35-45°C to obtain a primary cleaned strip;
[0099] The primary cleaning tape is fed into an annealing furnace at a tape speed of 1.0 m / min and continuously annealed at 1050° C. to obtain a primary annealing tape after cooling;
[0100] S7.2, the primary annealed strip is fed into a rolling mill for secondary cold rolling, the secondary cold rolling reduction is 52%, the rolling tension is 24KN, three passes are adopted and the first pass reduction ratio is ≮22%, and a secondary cold rolled strip with a thickness of 0.85mm is obtained;
[0101] The secondary cold-rolled strip is degreased and cleaned with hot alkaline water at 35-45°C to obtain a secondary cleaned strip;
[0102] The secondary cleaning tape is fed into the annealing furnace at a tape speed of 2.8 m / min and continuously annealed at 1050°C to obtain a secondary annealing tape after cooling;
[0103] S7.3, the secondary annealed strip is sent to the rolling mill for three cold rolling, the three cold rolling reduction rate is 48%, the rolling tension is 24KN, three passes are used and the first pass reduction rate is ≮20%, and a three cold rolled strip with a thickness of 0.35mm is obtained:
[0104] The secondary cold-rolled strip is degreased and cleaned with hot alkaline water at 35-45°C to obtain a triple-cleaned strip:
[0105] The tertiary cleaned strip is fed into the annealing furnace at a strip speed of 7.8 m / min and continuously annealed at 1050° C. After cooling, a tertiary annealed strip is obtained, i.e., a high nitrogen duplex stainless steel strip.
[0106] In step S7, high-purity nitrogen is used for purging and cooling after continuous annealing, the purging pressure is 0.35 MPa, and the cooling rate is 140°C / min.
[0107] Example 2
[0108] The difference between Example 2 and Example 1 is that a three-time cold-rolled strip with a thickness of 0.49 mm is obtained.
[0109] Example 3
[0110] Compared with Example 1, Example 3 is different in that a three-time cold-rolled strip with a thickness of 0.54 mm is obtained.
[0111] Example 4
[0112] The difference between Example 4 and Example 1 is that a three-time cold-rolled strip with a thickness of 0.55 mm is obtained.
[0113] Comparative Example 1
[0114] Compared with Example 1, Comparative Example 1 differs in that the final forging temperature and the final rolling temperature are both ≥ 960° C.; and a tertiary cold-rolled strip with a thickness of 0.51 mm is obtained.
[0115] Comparative Example 2
[0116] Compared with Example 1, Comparative Example 2 differs in that: after continuous annealing, 0.35 MPa compressed air is used for purging and cooling; and a tertiary cold-rolled strip with a thickness of 0.54 mm is obtained.
[0117] The chemical compositions of the high nitrogen duplex stainless steel strips prepared in Examples 1 to 4 and Comparative Examples 1 and 2 were tested, as shown in Table 1.
[0118] Table 1: Chemical composition of high nitrogen duplex stainless steel strips in Examples 1 to 4, Comparative Examples 1 and 2
[0119]
[0120] The room temperature tensile strength, room temperature yield strength, room temperature elongation, ferrite content, welding strength, -40°C impact resistance and 50±2°C pitting corrosion rate of the high nitrogen duplex stainless steel strips prepared in Examples 1 to 4 and Comparative Examples 1 and 2 were tested respectively, and the test results are shown in Table 2.
[0121] Table 2: Performance test table of high nitrogen duplex stainless steel strips in Examples 1 to 4 and Comparative Examples 1 and 2
[0122]
[0123] Combining Table 1 and Table 2, it can be seen that increasing the N content in the strip can improve the strength of the high nitrogen duplex stainless steel strip, namely the tensile strength, yield strength and welding strength, and can also improve the corrosion resistance of the strip.
[0124] As shown in Table 2, the high nitrogen duplex stainless steel strip prepared by the present invention has a tensile strength of ≥1150MPa, a yield strength of ≥806MPa, and an elongation of ≥47%. The ferrite content is ≥40.8%, the welding strength is ≥1001MPa or more; the impact toughness at -40℃ is ≥131J, and the pitting corrosion rate at 50±2℃ is 5.09-6.27g / m2 / h;
[0125] Moreover, compared with the control example, the tensile strength is increased by 34.3%, the yield strength is increased by 43%, the elongation is increased by 9%, the ferrite content is increased by 12.7%, the welding strength is increased by 36.7%, the -40℃ impact toughness is increased by 10.1%, and the pitting corrosion rate at 50±2℃ is reduced by 43.5%.
[0126] In other embodiments of the present invention, the steel billet is subjected to multi-forging, and the deformation amount of the multi-forging is 20%-40%.
[0127] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A high nitrogen duplex stainless steel, characterized in that: In terms of mass percentage, its chemical composition includes: N: 0.15-0.35%, Cr: 24.5-26.5%, Ni: 8.0-11.0%, Mo: 3.4-3.9%, Mn: 1.5-3.5%, C≤0.001%, Si≤0.20%, P≤0.02%, S≤0.01%, and the balance Fe.
2. The high nitrogen duplex stainless steel according to claim 1, characterized in that: In terms of mass percentage, its chemical composition includes: N: 0.23-0.28%, Cr: 24.9-25.2%, Ni: 8.92-9.15%, Mo: 3.7-3.75%, Mn: 2.65-2.69%, C≤0.001%, Si≤0.20%, P≤0.02%, S≤0.01%, and the balance Fe.
3. The high nitrogen duplex stainless steel according to claim 1, characterized in that: In terms of mass percentage, its chemical composition includes: N: 0.28-0.33%, Cr: 25.2-25.6%, Ni: 8.41-8.95%, Mo: 3.75-3.77%, Mn: 2.69-2.73%, C≤0.001%, Si≤0.20%, P≤0.02%, S≤0.01%, and the balance Fe.
4. A method for preparing a high nitrogen duplex stainless steel strip, characterized in that: The steps include: S1. Prepare the charge, melt the charge, and obtain a steel billet with the chemical composition after cooling; S2. Grinding the surface of the steel billet to remove defects on the surface of the steel billet; S3, preheating the steel billet after grinding at 560-640°C for 30 min, then heating the steel billet to 1180-1240°C at a heating rate of 150-200°C / min and keeping it warm for 1 h; After the insulation is completed, the steel billet is forged with a deformation amount of 20%-40%, the start forging temperature is ≥1160℃, and the final forging temperature is ≥1040℃; After forging is completed, air cooling is performed to obtain the forging blank; S4, grinding the forging blank and blowing it with compressed air to remove the residual oxide scales from grinding; S5. Heat the forging blank to 1180-1240°C at a heating rate of 190-240°C / min and keep it at that temperature for 1 hour; After the heat preservation is completed, the forging billet is hot rolled, the starting rolling temperature is ≥1160°C, the final rolling temperature is ≥1040°C, and the hot rolling is completed and air-cooled to obtain a hot-rolled billet; S6, heating the hot rolled billet to 1070-1180° C., and performing a solution treatment on the hot rolled billet for 30-60 minutes; After the solution treatment, the hot rolled billet is immediately water cooled, and then the hot rolled billet is ground; S7. The hot-rolled billet is subjected to three cold rolling, degreasing and continuous annealing to obtain a high nitrogen duplex stainless steel strip.
5. The method for preparing a high nitrogen duplex stainless steel strip according to claim 4, characterized in that: In step S1, the furnace charge is metallic chromium, electrolytic nickel, metallic molybdenum, metallic manganese, pure iron and ferrochromium nitride with a particle size of ≯20 mm, and the nitrogen content in the ferrochromium nitride is greater than or equal to 10%.
6. The method for preparing a high nitrogen duplex stainless steel strip according to claim 4, characterized in that: In step S3, the steel billet is subjected to multi-forging, and the deformation amount of the multi-forging is 20%-40%.
7. The method for preparing a high nitrogen duplex stainless steel strip according to claim 4, characterized in that: In step S4, the pressure of the compressed air is 0.2-0.5 MPa.
8. The method for preparing a high nitrogen duplex stainless steel strip according to claim 4, characterized in that: In step S5, the forging billet is hot rolled, and the thickness of the hot rolled billet is 4.0-4.5 mm.
9. The method for preparing a high nitrogen duplex stainless steel strip according to claim 4, characterized in that: Step S7 is specifically as follows: S7.1, feeding the hot rolled slab into a rolling mill for primary cold rolling, wherein the reduction rate of the primary cold rolling is 50%-60%, the rolling tension is 40-60KN, four passes are adopted and the reduction rate of the first pass is ≮25%, and a primary cold rolled strip with a thickness of 1.62-2.25mm is obtained; The primary cold-rolled strip is degreased and cleaned using hot alkaline water at 35-45°C to obtain a primary cleaned strip; The primary cleaning tape is fed into the annealing furnace at a tape speed of 0.7-1.2 m / min, and continuously annealed at 1050°C, and a primary annealing tape is obtained after cooling; S7.2, feeding the primary annealed strip into a rolling mill for secondary cold rolling, wherein the secondary cold rolling reduction rate is 50%-55%, the rolling tension is 23-28KN, three passes are adopted and the first pass reduction rate is ≮22%, and a secondary cold rolled strip with a thickness of 0.75-1.13mm is obtained; The secondary cold-rolled strip is degreased and cleaned with hot alkaline water at 35-45°C to obtain a secondary cleaned strip; The secondary cleaning tape is fed into the annealing furnace at a tape speed of 2.0-3.0 m / min, and continuously annealed at 1050°C, and a secondary annealing tape is obtained after cooling; S7.3, the secondary annealed strip is sent to the rolling mill for three cold rolling, the three cold rolling reduction rate is 45%-52%, the rolling tension is 16-25KN, three passes are used for rolling and the first pass reduction rate is ≮20%, and the three cold rolling strip with a thickness of 0.35-0.55mm is obtained: The secondary cold-rolled strip is degreased and cleaned with hot alkaline water at 35-45°C to obtain a triple-cleaned strip: The tertiary cleaned strip is fed into an annealing furnace at a strip speed of 6.0-8.0 m / min and continuously annealed at 1050° C. After cooling, a tertiary annealed strip is obtained, i.e., a high nitrogen duplex stainless steel strip.
10. The method for preparing a high nitrogen duplex stainless steel strip according to claim 9, characterized in that: In step S7, high-purity nitrogen is used for purging and cooling after continuous annealing, the purging pressure is 0.2-0.5 MPa, and the cooling rate is 130-150°C / min; In terms of mass percentage, hot alkaline water at 35-45°C is a mixture of 30% sodium hydroxide and 70% tap water.
Citation Information
Cited By
Processing technology of high-strength corrosion-resistant nitrogen alloying stainless steel band
CN121250265A
Processing technology of high-strength corrosion-resistant nitrogen alloyed stainless steel strip
CN121250265B